Improving Student Learning Outcomes in Islamic Education Learning Through the Drill Method at SD 173651 Pintu Pohan - Andalina, Sri; Magdalena, Toria; Siallagan, Desi A (Jurnal Pendidikan Profesi Guru, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning using the drill method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were high school students. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the drill method can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 45.59%, the first cycle 63.87% and in the second cycle it increased to 97.42%. Thus, the use of videos can be used as an alternative to improve student learning outcomes in Islamic religious education learning.